1995
DOI: 10.1111/j.1365-2273.1995.tb01850.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma catecholamine levels during functional endoscopic sinus surgery

Abstract: Plasma adrenaline and noradrenaline concentrations were measured in 10 consecutive patients during functional endoscopic sinus surgery (FESS). Surgery was preceded by nasal packing with 5 ml 2% cocaine solution, followed by infiltration with 1:80,000 adrenaline and 2% lignocaine. All patients showed a marked rise in plasma adrenaline concentration within 4 min of commencing infiltration, which was not related to the patient's sex, age, weight, the total amount injected, nor the amount injected into the nose. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
40
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 6 publications
1
40
1
Order By: Relevance
“…On the other hand, frequent using these types of agencies bring about problems for example gastrointestinal irritability, tendency to bleed, in addition to allergy symptoms, that might reduce their use [12]. John et al [13] reported that infiltration technique is better than surface anesthesia in pain control but there was no difference in blood loss between two technique. Temple et al [9] demonstrated that there were no difference in pain after turbinectomy between topical adrenaline applying and injecting adrenaline and xylocaine.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, frequent using these types of agencies bring about problems for example gastrointestinal irritability, tendency to bleed, in addition to allergy symptoms, that might reduce their use [12]. John et al [13] reported that infiltration technique is better than surface anesthesia in pain control but there was no difference in blood loss between two technique. Temple et al [9] demonstrated that there were no difference in pain after turbinectomy between topical adrenaline applying and injecting adrenaline and xylocaine.…”
Section: Discussionmentioning
confidence: 99%
“…Often these studies tend to associate more than one vasoconstritor, usually adrenaline and cocaine. 14,16 In our view, not enough information is available about the behavior of each vasoconstritor singly on the nasal mucosa; thus, such associations are not beneficial for research purposes, since they complicate data analysis. This is the first paper that we know of comparing adrenalin solutions (not associated with other vasoconstritors) used only topically on the nasal mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…Comparing the results of published papers is difficult, since each deals with different surgical procedures (septoplasty, 2,3,6 turbinectomy, 5 endoscopic surgery of the lateral wall of the nose 4,12 ), a variety of administration methods (submucosa, topical or both 4,6,12,13,14 ), and vasoconstritors (cocaine, adrenalin, phenylephrin, 15 oxymetazoline 12 ). Often these studies tend to associate more than one vasoconstritor, usually adrenaline and cocaine.…”
Section: Discussionmentioning
confidence: 99%
“…Injected vasoconstrictors can lead to serious side effects. After injection of lignocaine with adrenaline, plasma levels of adrenaline reach a peak value that is highly variable and not related to the amount injected into the nasal mucosa [18]. Also, with topical anesthesia with cocaine, idiosyncratic absorption can occur.…”
Section: Discussionmentioning
confidence: 99%